Productivity and Tax Evasion - Dabla-Norris, Era (IMF Working Papers; Working Paper ;, 2019)
The extent of tax compliance has important implications for revenue yield, efficiency and the fairness of any tax system. Tax evasion undermines revenue collection, distorts competition, and undermines a country's development prospects. In this paper, we investigate whether higher productivity causally leads to lower tax evasion. We first present stylized facts consistent with this view and develop a model that illustrates one potential transmission channel. Second, we test the model predictions at the firm level using the self-reported share of declared income as proxy for tax evasion for a large sample of emerging and developing economies. Our results suggests that productivity improvements by firms can lead to lower tax evasion.